Key Issues and Opportunities in the Initial Identification and Classification of English Learners. Issue 1 (4th April 2016) - Lopez, Alexis A.; Pooler, Emilie; Linquanti, Robert
Abstract: English learners (ELs) require access to appropriate instructional services that match their strengths and needs to have an equal opportunity to achieve the same academic standards as other students. If ELs are not properly identified and classified, they may be excluded from services that would better help them meet high academic standards, and they may not receive optimal supports to advance both linguistically and academically. Thus, it is critical to accurately and properly identify newly enrolled students who are in need of supplemental instruction and support. The purpose of this report is to identify issues in current initial English‐language proficiency assessment practices used to determine initial EL classification and offer recommendations to strengthen the policies, process, and tools used in the identification and classification of ELs. Abstract : Report Number: ETS RR‐16–09